2012
DOI: 10.1021/es300593a
|View full text |Cite
|
Sign up to set email alerts
|

Development and Calibration of a Passive Sampler for Perfluorinated Alkyl Carboxylates and Sulfonates in Water

Abstract: Perfluorinated chemicals (PFCs) are emerging environmental contaminants with a global distribution. Due to their moderate water solubility, the majority of the environmental burden is assumed to be in the water phase. This work describes the application of the first passive sampler for the quantitative assessment of concentrations of perfluorinated alkylcarboxylates (PFCAs) and sulfonates (PFSAs) in water. The sampler is based on a modified Polar Organic Chemical Integrative Sampler (POCIS) with a weak anion e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
59
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 47 publications
5
59
1
1
Order By: Relevance
“…They concluded that the MAX and MCX versions showed little advantage over HLB in natural waters. Kaserzon et al 103 used a weak anion exchange sorbent (Strata XAW) for sampling perfluorinated alkyl carboxylates and sulfonates, based on its superiority for sequestering the shorter‐chain compounds. Other types of membrane‐covered, sorbent‐based samplers for polar compounds are also described in the literature, for example, coconut charcoal in teabag filter papers for nitrosamines 104 and sorbent‐based samplers to target microalgal biotoxins 105–107.…”
Section: Reported Applications and Usementioning
confidence: 99%
“…They concluded that the MAX and MCX versions showed little advantage over HLB in natural waters. Kaserzon et al 103 used a weak anion exchange sorbent (Strata XAW) for sampling perfluorinated alkyl carboxylates and sulfonates, based on its superiority for sequestering the shorter‐chain compounds. Other types of membrane‐covered, sorbent‐based samplers for polar compounds are also described in the literature, for example, coconut charcoal in teabag filter papers for nitrosamines 104 and sorbent‐based samplers to target microalgal biotoxins 105–107.…”
Section: Reported Applications and Usementioning
confidence: 99%
“…Modified POCIS Samplers. Modified POCIS passive samplers were constructed as described previously 19 with the exception of the sorbent phase used. To extend the duration of the kinetic/linear uptake stage, the modified POCIS contained an increased sorbent mass (viz.…”
Section: Introductionmentioning
confidence: 99%
“…There are 170 many variations of this including the use of in situ samplers which are programmed to turn on and 171 off underwater, and in line systems bringing seawater directly into clean rooms on ships (Table 4). hydrophilic POPs such as HCH isomers, endosulfan and dieldrin, as well as anionic PFOS [35] 181 (Table 4) …”
mentioning
confidence: 99%